Fatores determinantes da necessidade de capital de giro corporativa - Pires, Clênia de Oliveira (Universidade do Vale do Rio dos Sinos, 2013)
This thesis aims to identify and analyze the determinants of the working capital requirement corporate, from robust theories of finance (Theory of Asymmetric Information, Agency Theory, Pecking Order Theory and Theory of Financial Distress) and empirical studies that also had as object the WCR. Therefore, this study was based on a panel data unbalanced, with information of 222 Brazilian companies non-financial with stocks listed on the BM&FBOVESPA and presents in Compustat Database, for a period of 11 years (2000 to 2010), totaling 2278 observations. We tested different variables, using linear regression models of different complexities. From the results of the final regression, generated by Dynamic Panel, ten factors determinants of the working capital requirement corporate were identified, all significants. The model evidences the importance of WCR last year in explaining the WCR this year and shows that larger companies, with more volatile sales, higher free cash flow, higher debt ratio and financially distressed adopt a working capital requirement proportionally reduced, making it more efficient in its management of working capital. Moreover, the evidence shows that a higher contribution margin, a higher rate market-to-book and the presence of annual compensation tied to earnings lead to an increased working capital requirement corporate. Furthermore, the results suggest that a lower country risk encourages investment in working capital, showing that company exogenous factors also determine the volume of your WCR. Thus, this thesis aims to contribute to future research, since it is the first to investigate the determinants of the net investment in operating working capital from the perspective of four robust theories of finance.
Keywords: Necessidade de capital de giro; Determinantes; Teorias financeiras; Painel dinâmico; Working capital requirement; Determinants; Financial theories; Dynamic panel; ACCNPQ::Ciências Sociais Aplicadas::Ciências Contábeis